Repostioning of Telemedicine in Cardiovascular World Post-COVID-19 Pandemic - Sharma, Kamal; Patel, Zeel; Patel, Smeet; Patel, Kalpen; Dabhi, Shweta; Doshi, Jinish; Amdani, MohmadSabir; Shah, Darshini; Patel, Dhyanee; Konat, Ashwati (Frontiers in Cardiovascular Medicine, 2022)
Background During the COVID-19 pandemic, telemedicine is a quickest expanding service solution to provide improved access to sophisticated healthcare that is efficient, cost-effective, and time-consuming. Methods This analysis is evaluated on the basis of several studies that look at the history, benefits, various techniques, challenges, uses, and impact of telemedicine in the treatment of heart failure and cardiac rehabilitation as during COVID-19 outbreak. Results Patients avoided or refused medical treatment during COVID-19 pandemic despite the risk of illness and the threat of infections spreading. Telemedicine has become a non-traditional form of care delivery due to better access and high-end technologies such as virtual consultations, face-to-face video, smartphone visits, two-way text communication, distant patient history, and distal characteristic assessment. Remote monitoring can help manage cardiovascular disease risk factors and increase patient participation in blood pressure, heart failure data, and workout or other activity progress. Conclusion Based on the findings of past studies, we can infer that telemedicine is still an emerging subject in the treatment and management of cardiovascular disease. Telemedicine and similar technologies will also revolutionize healthcare services by expanding their reach and providing a big pool of database for better research and analysis.